Immediate versus deferred zidovudine (AZT) in asymptomatic or mildly symptomatic HIV infected adults. - Darbyshire, J; Foulkes, M; Peto, R; Duncan, W; Babiker, A; Collins, R; Hughes, M; Peto, T; Walker, A (2000)
BACKGROUND: Zidovudine (AZT) monotherapy was the first antiretroviral drug to be tested widely. Subsequent trials in asymptomatic or early symptomatic HIV infection indicated short-term delays in disease progression with AZT, but not improved survival. OBJECTIVES: To assess the effects of immediate versus deferred zidovudine (AZT) on HIV disease progression and survival. SEARCH STRATEGY: Investigators and pharmaceutical companies were contacted, and MEDLINE searches were supplemented by searching conference abstracts. SELECTION CRITERIA: Randomised controlled trials comparing immediate versus deferred AZT in participants without AIDS which prospectively collected deaths and new AIDS events. DATA COLLECTION AND ANALYSIS: Individual patient data with, wherever possible, follow-up obtained beyond that previously published was obtained and checked for internal consistency and consistency with any published reports; any apparent discrepancies were resolved with the trialists. Time to death and to disease progression (defined as a new AIDS-defining event or prior death) were analysed on an intention to treat basis, stratified to avoid direct comparisons between participants in different trials. MAIN RESULTS: Nine trials were included in the meta-analysis. During a median follow-up of 50 months, 1908 individuals developed disease progression, of whom 1351 died. In the deferred group, 61% started antiretroviral therapy (median time to therapy 28 months, which was AZT monotherapy in 94%). During the first year of follow-up immediate AZT halved the rate of disease progression (P<0.0001), increasing the probability of AIDS-free survival at one year from 96% to 98%, but this early benefit did not persist: after 6 years AIDS-free survival was 54% in both groups, and at no time was there any difference in overall survival, which at 6 years was 64% with immediate and 65% with deferred AZT (rate ratio [RR] 1.04, 95% confidence interval [CI] 0. 94 to 1.15). REVIEWER'S CONCLUSIONS: Although immediate use of AZT halved disease progression during the first year, this effect was not sustained, and there was no improvement in survival in the short or long term.